2014
DOI: 10.1121/1.4895698
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of preserving stationary and time-varying formant structure in alternative representations of speech: Implications for cochlear implants

Abstract: Cochlear implants have improved speech recognition for deaf individuals, but further modifications are required before performance will match that of normal-hearing listeners. In this study, the hypotheses were tested that (1) implant processing would benefit from efforts to preserve the structure of the low-frequency formants and (2) time-varying aspects of that structure would be especially beneficial. Using noise-vocoded and sine-wave stimuli with normal-hearing listeners, two experiments examined placing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Other authors have addressed that question with relatively static spectral cues, such as distinguishing time-invariant vowel formants. By creating synthetic stimuli with dynamic formant information, we focused on the dynamic spectral information, which is more characteristic of that which would occur in everyday speech and which provides a higher level of information (Nittrouer, Lowenstein, Wucinich, & Tarr, 2014;Viswanathan, Magnuson, & Fowler, 2014). .…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have addressed that question with relatively static spectral cues, such as distinguishing time-invariant vowel formants. By creating synthetic stimuli with dynamic formant information, we focused on the dynamic spectral information, which is more characteristic of that which would occur in everyday speech and which provides a higher level of information (Nittrouer, Lowenstein, Wucinich, & Tarr, 2014;Viswanathan, Magnuson, & Fowler, 2014). .…”
Section: Discussionmentioning
confidence: 99%
“…The authors additional found interactions with word difficulty: easy words (high-frequency, low phonological neighborhood density) required fewer vocoder channels for recognition than hard words (low-frequency, high neighborhood density) (see Dorman et al (1998);Eisenberg et al (2002) and Roman et al (2017) for similar discrepancies between "easy" and "hard" word recognition among from 5-14-year-olds listening to 4-channel vocoded stimuli). Children's need for increased spectral resolution is also relevant for individual vowel sounds as well, although the patterns of phoneme confusion are similar to those of adults (Jahn et al, 2019) Other vocoding work with children has extended beyond spectral degradation to manipulate channel configuration, namely designing vocoder channels that do or do not preserve formant structure (Nittrouer et al, 2014a) . Here the assumption is that earlier in life, CI listeners might rely relatively more on formant structure cues to process speech and language, and that this could shift with age and experience, just as phonetic cue-weighting strategies change markedly through early adolescence in children with TH (Hazan and Barrett, 2000).…”
Section: B Vocoders In Developmental Researchmentioning
confidence: 99%
“…However, there were no differences between vocoder conditions by age. Thus, all CI recipients' speech recognition could benefit from speech-specific processing strategies (Nittrouer et al, 2014a).…”
Section: B Vocoders In Developmental Researchmentioning
confidence: 99%